2020
DOI: 10.1016/j.yhbeh.2020.104814
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the toll of the COVID-19 pandemic on publishing: Evidence from submissions to Hormones and Behavior

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…While it is too early to fully understand the effects of the pandemic on scholarly publishing, preliminary observations have suggested that submissions to journals have generally increased during the pandemic (Bell & Fong, 2020; Squazzoni et al, 2020), likely because many researchers lost access to their laboratories for some time and switched over to writing papers (Aubry et al, 2020). However, analyses of submissions to preprint servers (Cui et al, 2020; King & Frederickson, 2020; Viglione, 2020; Vincent‐Lamarre et al, 2020) and journals (Bell & Fong, 2020; Kibbe, 2020; McCormick, 2020; Muric et al, 2020; Shurchkov, 2020; Squazzoni et al, 2020; but see Dolan & Lawless, 2020) suggest that submissions from women have either grown less than those from men, or have even declined, though the magnitude and presence of the gender difference has varied among disciplines. A decrease in the proportion of submissions authored by women suggests that the productivity of female scholars has been more substantially impacted by pandemic disruptions, compared to the productivity of male scholars, likely because many communities have closed primary schools, childcare facilities, and other public and private institutions that help manage children (Alon et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While it is too early to fully understand the effects of the pandemic on scholarly publishing, preliminary observations have suggested that submissions to journals have generally increased during the pandemic (Bell & Fong, 2020; Squazzoni et al, 2020), likely because many researchers lost access to their laboratories for some time and switched over to writing papers (Aubry et al, 2020). However, analyses of submissions to preprint servers (Cui et al, 2020; King & Frederickson, 2020; Viglione, 2020; Vincent‐Lamarre et al, 2020) and journals (Bell & Fong, 2020; Kibbe, 2020; McCormick, 2020; Muric et al, 2020; Shurchkov, 2020; Squazzoni et al, 2020; but see Dolan & Lawless, 2020) suggest that submissions from women have either grown less than those from men, or have even declined, though the magnitude and presence of the gender difference has varied among disciplines. A decrease in the proportion of submissions authored by women suggests that the productivity of female scholars has been more substantially impacted by pandemic disruptions, compared to the productivity of male scholars, likely because many communities have closed primary schools, childcare facilities, and other public and private institutions that help manage children (Alon et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the obvious effects on women and early career researchers, other studies have emphasized the long-term impacts on older adults, particularly through the creation of workforce bottlenecks with the delay in time to retirement preventing jobs opening up to new grad-uates [18]. Overall submissions to academic journals show declines in submissions by female authors [19,20]. Submissions across pre-print websites (e.g., bioRxiv) also show that women were submitting at a lower rate in the first two months of the pandemic than other groups [21].…”
Section: Introductionmentioning
confidence: 99%
“…Since the start of the COVID-19 pandemic and the lockdowns and social distancing policies most countries have implemented to try to curtail it, anecdotal (social media), submissions, and pre-print evidence has suggested that women in science have been submitting fewer manuscripts than their male counterparts (Cui et al, 2020; McCormick, 2020 , Viglione, 2020 ). Recently published articles and editorials from a handful of journals in the biological sciences now show that this gendered detrimental impact on publishing capacity is being reflected in peer reviewed publication rates in some journals as well ( Pinho-Gomes et al, 2020 ), although Neuropsychopharmacology had seen no change by June 2020 ( Jordan and Carlezon, 2020 ).…”
mentioning
confidence: 99%